THE EFFECT OF INTERACTIVE MEDIA WORDWALL ASSISTED BY TALKING STICK ON STUDENT LEARNING IMPROVEMENT AND OUTCOMES AT STATE SENIOR HIGH SCHOOL 01 KUNIR – LUMAJANG - Izzah, Nury Yahdinil; Muali, Chusnul; Andre Setiawan, Muhammad Bakron; Alfaridli, Muhammad Alfi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The rapid development of technology should make students' learning outcomes increase, but in reality, what happens at SMA Negeri 01 Kunir - Lumajang is that students' learning outcomes are low or tend to be unstable. This is apparently caused by the unbalanced number of educators with classes that must be taught. As a result, educators are overwhelmed, and the learning process is boring due to the lack of preparation of educators in using learning models and media.From the description above, the researcher intends to conduct a study using interactive-based Wordwall learning media with the help of Talking Stick to find out whether there is an effect of interactive Wordwall media assisted by Talking Stick on improving student learning outcomes at SMA Negeri 01 Kunir - Lumajang.The method used in this research is Quasi Experimental Design with Nonequivalent Control Group Design type. The technique used to determine the research sample is the Random Sampling technique. Before applying Wordwall interactive media assisted by Talking Stick to the experimental class, the control class and experimental class were both given a pretest to determine the initial ability of the two samples. And it turns out that the results of the two classes are both normally distributed and homogeneous variants. After the application of interactive media Wordwall with Talking Stick, followed by giving the final question (posttest) in the control and experimental classes to determine the results of the application.The result is an increase in the learning value of students in the experimental class. Calculation of values using SPSS shows a very significant difference, learning outcomes with a value of Asymp. Sig (2-tailed) of 1.000> 0.05, meaning that the experimental class scores tend to be higher than the control class. So it can be concluded that the use of interactive media Wordwall assisted by Talking Stick has an influence on improving student learning outcomes, especially in class XI students of SMA Negeri 01 Kunir - Lumajang with the material of tolerance and maintaining human life.